2015
DOI: 10.2147/copd.s91176
|View full text |Cite
|
Sign up to set email alerts
|

The one repetition maximum test and the sit-to-stand test in the assessment of a specific pulmonary rehabilitation program on peripheral muscle strength in COPD patients

Abstract: BackgroundIndividuals with COPD may present reduced peripheral muscle strength, leading to impaired mobility. Comprehensive pulmonary rehabilitation (PR) should include strength training, in particular to lower limbs. Furthermore, simple tools for the assessment of peripheral muscle performance are required.ObjectivesTo assess the peripheral muscle performance of COPD patients by the sit-to-stand test (STST), as compared to the one-repetition maximum (1-RM), considered as the gold standard for assessing muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 31 publications
11
86
3
7
Order By: Relevance
“…Compared with previous studies in COPD, 12,28 our subjects had relatively preserved lower-limb strength, and much lower inter-individual variability was found for STS performance and quadriceps strength, thereby potentially weakening the association between these parameters. Moreover, previous studies did not use a reference method to evaluate limb muscle strength (eg, manual force testing 28 or one-repetition maximum 12 ), potentially leading to inaccuracies affecting the relationship with STS performance. Overall, the moderate association between the STS test and quadriceps force in our study supports their convergent validity.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Compared with previous studies in COPD, 12,28 our subjects had relatively preserved lower-limb strength, and much lower inter-individual variability was found for STS performance and quadriceps strength, thereby potentially weakening the association between these parameters. Moreover, previous studies did not use a reference method to evaluate limb muscle strength (eg, manual force testing 28 or one-repetition maximum 12 ), potentially leading to inaccuracies affecting the relationship with STS performance. Overall, the moderate association between the STS test and quadriceps force in our study supports their convergent validity.…”
Section: Discussioncontrasting
confidence: 79%
“…5 Based on significant associations with quadriceps strength, 12,28 the STS test has been proposed as a simple measure of lower-limb strength. We expressed STS repetitions as a product of body weight because this factor clearly influences STS performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise capacity was assessed with the 30-second sit-to-stand (STS) test, a field exercise test, which has been accepted as an indicator of functional status for elderly people. It is able to identify peripheral muscle weakness in patients with COPD (19). Participants were asked to stand up and sit down landing firmly, as fast as possible, without using the arms during 30seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown improvements in physical function with endurance training but not strength training (16–18), with strength training but not endurance training (19,20),whereas others have shown improvements with both (21,22). Discordant results are also noted when examining improvements in health related quality of life, and the quality of evidence from studies supporting one type of training over the other is often poor (23).…”
Section: Introductionmentioning
confidence: 99%